x + 3 = 0, x = 3
x + 3 = 0
Putting x = 3
3 + 3 = 0
6 = 0
It is false.
So, equation is not satisfied
(ii) x + 3 = 0, x = 3
x + 3 = 0
Putting x = 0
0 + 3 = 0
3 = 0
It is false.
So, equation is not satisfied
(ii) x + 3 = 0, x = 3
x + 3 = 0
Putting x = 0
0 + 3 = 0
3 = 0
It is false.
So, equation is not satisfied
(iii) x + 3 = 0, x = 3
x + 3 = 0
Putting x = 3
3 + 3 = 0
3 3 = 0
0 = 0
It is True.
So, equation is satisfied
(iv) x 7 = 1, x = 7
x 7 = 1
Putting x = 7
7 7 = 1
0 = 1
It is false.
So, equation is not satisfied
(v) x 7 = 1, x = 8
x 7 = 1
Putting x = 8
8 7 = 1
1 = 1
It is True.
So, equation is satisfied
(vi) 5x = 25, x = 0
5x = 25
Putting x = 0
5(0) = 25
0 = 25
It is False.
So, equation is not satisfied
(vii) 5x = 25, x = 5
5x = 25
Putting x = 5
5(5) = 25
25 = 25
It is True.
So, equation is satisfied
(viii) 5x = 25, x = 5
5x = 25
Putting x = 5
5( 5) = 25
25 = 25
It is False.
So, equation is not satisfied
(ix) /3 = 2, m = 6
/3 = 2
Putting m = 6
( 6)/3 = 2
2 = 2
It is False.
So, equation is not satisfied
(x) /3 = 2, m = 0
/3 = 2
Putting m = 0
0/3 = 2
0 = 2
It is False.
So, equation is not satisfied
(xi) /3 = 2, m = 6
/3 = 2
Putting m = 6
6/3 = 2
2 = 2
It is True.
So, equation is satisfied

Made by

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths and Science at Teachoo.